Mapping Groundwater Potential Zone Based On Remote Sensing And Gis Using Analytical Hierarchy Process (Ahp) In Tana Righu, West Sumba, Indonesia - Yacob Victor Hayer; Arnoldus Nama Nama; Dedy Ardianto Fallo (P3M- Politeknik Negeri Kupang, 2023)
This study aims to delineate groundwater potential zones in Tana Righu. Multiple thematic maps were prepared using RS and GIS techniques and was assigned suitable weights on the Saatyâ€™s scale. The assigned weights of the thematic maps were then normalized using the AHP technique. Ultimately, these thematic maps were integrated with a weighted overlay technique in GIS. The results showed that about 42% of the study area has â€œmoderateâ€ potential; 35.86% of the study area has â€œhighâ€ potential; 28,82% of the study area has â€lowâ€ potential. 3.57.1% of the study area has â€œvery highâ€ potential; and 1.56.1% of the study area The â€œvery lowâ€ potential. Overall, this study provides more efficient approach to mapping the potential groundwater availability. The results of this study are expected to assist in the planning, management and better utilization of groundwater resources.